2018
DOI: 10.1093/schbul/sby180
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Paranoia: Prevalence, Structure, and Causal Mechanisms

Abstract: Background Adolescence can be a challenging time, characterized by self-consciousness, heightened regard for peer acceptance, and fear of rejection. Interpersonal concerns are amplified by unpredictable social interactions, both online and offline. This developmental and social context is potentially conducive to the emergence of paranoia. However, research on paranoia during adolescence is scarce. Method Our aim was to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…The B-CAP has concurrent validity with other measures of paranoia, with data from Bird et al (2019) showing a correlation of r=0.84 (p<0.001) with the paranoia subscale of the Specific Psychotic Experiences Questionnaire (SPEQ; Ronald et al 2014) and r=0.68 (p<0.001) with the Social Mistrust Scale (SMS; Wong et al 2014). Although all paranoia measures are limited in their ability to determine whether thoughts are truly unfounded, we have shown that B-CAP scores are moderate correlated (r=0.41, p<0.001) with participant ratings on a visual analogue scale (VAS) that they are 'more fearful of others than they should be' (Bird et al 2019). This was significantly larger than the small correlation of r=0.25 between the same VAS rating and bullying scores (z=5.35, p<0.001).…”
Section: Assessmentsmentioning
confidence: 92%
“…The B-CAP has concurrent validity with other measures of paranoia, with data from Bird et al (2019) showing a correlation of r=0.84 (p<0.001) with the paranoia subscale of the Specific Psychotic Experiences Questionnaire (SPEQ; Ronald et al 2014) and r=0.68 (p<0.001) with the Social Mistrust Scale (SMS; Wong et al 2014). Although all paranoia measures are limited in their ability to determine whether thoughts are truly unfounded, we have shown that B-CAP scores are moderate correlated (r=0.41, p<0.001) with participant ratings on a visual analogue scale (VAS) that they are 'more fearful of others than they should be' (Bird et al 2019). This was significantly larger than the small correlation of r=0.25 between the same VAS rating and bullying scores (z=5.35, p<0.001).…”
Section: Assessmentsmentioning
confidence: 92%
“…The final 18 items were selected from a broader item pool following exploratory and confirmatory factor analysis. The final hierarchical model of a second-order paranoia factor and three sub-factors of social harm, conspiracy ideas, and physical threat showed excellent fit statistics (Bird et al 2019).…”
Section: Assessmentsmentioning
confidence: 94%
“…Participants from the general population were recruited from a secondary school in Leicestershire, United Kingdom, as reported in Bird et al (2019). All pupils aged 11-15 years were invited to take part using opt-out parental consent and pupils who provided written assent completed the questionnaire as part of the larger study pack within a 60-minute lesson.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations